2020
DOI: 10.1111/eff.12536
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes reveal niche segregation between native and non‐native Hoplias in a Neotropical floodplain

Abstract: We investigated whether isotopic niche partitioning could mediate the coexistence between native (Hoplias sp. B) and non‐native (Hoplias mbigua) trahira in a Neotropical floodplain. We hypothesised that during the dry season both species inhabit isolated sites (i.e. lakes) and thus rely on distinct food resources to sustain their coexistence. We found evidence of trophic segregation among native and non‐native freshwater fish in the Upper Paraná River, Brazil. Even though both species rely on the same primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…This is because populations of P. lineatus were still synchronised in pairs of sites where R. vulpinus abundances were negatively correlated (i.e., between sites in the Ivinhema and Paraná rivers). In the case of A. lacustris and Hoplias sp.2, both species inhabit lentic waters and feed mainly on invertivorous fishes (Alves et al, 2020;Luz-Agostinho et al, 2008;Pereira et al, 2017;Piana et al, 2006), probably competing for resources to some degree. Haynes et al (2009) demonstrated that synchrony in basal resources driven by regional stochasticity can propagate through the food web causing predator populations to be synchronised as well.…”
Section: Mechanisms Of Spatial Synchronymentioning
confidence: 99%
“…This is because populations of P. lineatus were still synchronised in pairs of sites where R. vulpinus abundances were negatively correlated (i.e., between sites in the Ivinhema and Paraná rivers). In the case of A. lacustris and Hoplias sp.2, both species inhabit lentic waters and feed mainly on invertivorous fishes (Alves et al, 2020;Luz-Agostinho et al, 2008;Pereira et al, 2017;Piana et al, 2006), probably competing for resources to some degree. Haynes et al (2009) demonstrated that synchrony in basal resources driven by regional stochasticity can propagate through the food web causing predator populations to be synchronised as well.…”
Section: Mechanisms Of Spatial Synchronymentioning
confidence: 99%
“…However, empirical findings indicate that not all syntopic, congeneric species can expand their diet breath in periods of greater diversity and abundance of resources (Correa and Winemiller 2014;Silva et al 2017;Neves et al 2018a, b). This may be related to the traits and food preferences of species, and thus be of further assistance to understanding species coexistence (Chesson 2000;Walker et al 2013;Alves et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the concept of the isotopic niche was proposed, in which the axes of the multidimensional space are isotopic values that record bionomic and scenopoetic ecological information (Newsome et al ., 2007). Several authors have demonstrated that the isotopic niche is an important tool for exploring resource partitioning (Alves et al ., 2020), ontogenetic dietary shifts (Soares et al ., 2021) and niche overlap (Pennock et al ., 2021). This tool is especially useful for predator species, where the isotopic niche can provide a quantitative estimate of the energetic contribution and trophic level of prey species.…”
Section: Introductionmentioning
confidence: 99%